Methylene Blue Reduction by Using Multistage Filtratio - Ouhood Hassan Saleh (Journal of Global Pharma Technology, 2016)
Slow sand filtration (SSF) is established and workable equipment for drinking water handling in small societies. However, this technology is sensible to depressed water temperatures which can result in reduced biological treatment, and excessive water turbidity quantities which can result in early plugging of the filters and repeated cleanup necessities, leading to raised danger of-pathogen development. Multistage filtration (MSF), comprising of roughing filtration (RF) tracked by slow sand filtration, can cope these treatment restrictions and give a strong treatment option for surface water resources of changeable water characteristics in northern climates, that normally water temperatures ranging below 2oC. The main objective of this study was to reveal the accuracy of MSF to remove methylene blue (MB) dye from water. In this research, testing was achieved by pilot multistage filtration system and fed with synthetic water polluted with MB dye. A system consisted from roughing filters filled with limestone media with different sizes and slow filter filled with glass media (SGF). The removal of MB of pilot plant was tested at hydraulic loading rates (0.5 and 1) m/h and initial concentration of (10 and 30) mg/L. The percentage reduction of MB dye reduced with increasing the influent MB dye concentration and increasing filtration rate. Limestone roughing filter (LRF) and slow glass filter gave good MB removal with average removal efficiency of 99.20% and 99.85% at least influent MB concentration of 10 mg/L and least velocity of 0.5 m/hr.Keywords: Slow sand filtration, Multistage-filtration (MSF), Roughing-filtration, Methylene Blue, Glass, Limestone.